Pengaruh Karakteristik Demografi, Persepsi Gaya Kepemimpinan Kepala Ruang Keperawatan dan Motivasi dengan Kinerja Perawat Pelaksana di Ruang Rawat Inap RSUD Kabupaten Batang - Projo Angkasa; Mardi Hartono; Ta' adi (Pena Medika Jurnal Kesehatan, 2011)
Background & Methode : This is explanatory research, with cross-sectional approach and the survey method. This study population was all the nurses at Inpatient Room of Batang Hospital, amount 199 people, and samples are nurses who had worked for at least 1 year, amount 133 respondents. Analysis of the correlation between the variables of age, working years, gender, marital status, perception of leadership style, and motivation with nurse’s performance using the chi-square test, whereas correlation between education and nurse’s performance using the Fisher Exact Test. To see the influence of demographic characteristics, perceptions of leadership, motivation of the nurse to performance logistic regression test.Result : The results of statistical tests showed that there were no correlation between age, working years, sex, education, marital status and perceptions of leadership style with performance of nursing room employers. Recommendations for nurses: a need to increase performance, especially by implementing standards of nursing care, for the management need of attention towards the motivation of the nurses, with a consistent application of rules, career development, incentives and infrastructure.Keywords : demographic characteristics, work motivation, leadership style.